ATATÜRK'S DEATH AND HIS FUNERAL CEREMONIES’ REFLECTIONS IN TURKEY - Uğur ÜÇÜNCÜ (Fırat University, 2021)
Mustafa Kemal Ataturk was born in Thessaloniki, 1881. He was son of one middle class family. He was very hardworking and his body was very healthy in childhood. Mustafa Kemal was a good commander completing training in the military schools. He successfully fulfilled important tasks at the Tripoli War, the Balkan Wars. He announced his name with the victories in the front of the Gallipoli, the First World War. He was a general because of the achievements in the Eastern Front. However, the Ottoman Empire was defeated in the First World War. The territory of the Ottoman Empire was occupied by the Allies after the Armistice of Mudros which it was signed on 30 October 1918. The National Struggle was launched under the leadership of Mustafa Kemal Pasha, because of the occupations. This struggle resulted in decisive Turkish victory. The whole world knew the name of Mustafa Kemal Pasha at present. After 1922, his direction of the statesman was very intense. He turned his country to a modern state with the revolutions. In this respect, He gained respectability of the whole world. The the Grand National Assembly of Turkey gave him the surname Ataturk in 1934. Hard-working process throughout his life caused various illnesses in his body. Cirrhosis disease was the worst of these diseases. Cirrhosis disease weakened Ataturk’s body. Ataturk died on November 10, 1938 at 9.05 in spite of his doctors’ all treatment efforts. Ataturk’s death caused sadness in Turkey and abroad. His funeral ceremony was done with the attention of the public and foreign visitors. In this study, it will try to put forward the last days of Ataturk, his death, his funeral ceremony and the effects of his death.